Identity of a Soviet Town: from the Garden City by an Englishman E. Howard to the Socialist City by a German E. May (Shcheglovsk-Kemerovo, Stalinsk-Novokuznetsk, Novonikolaevsk-Novosibirsk) - Mark Meerovich (Проект Байкал, 2014)
The article considers peculiarities of planning development of new industrial Western Siberian cities in the 1930s, which occurred during realization of the industrialization programme. It is assumed that those cities resemble each other like twins. They have neither identity nor any specific qualities, because in the frameworks of the Soviet town-planning policy the same planning postulates were compulsorily applied to all newly-built socialist cities, and recognition of local conditions was relegated to the background or sacrificed for planning stereotypes. Those planning stereotypes and postulates of the Soviet town-planning policy are thoroughly described in the article through an example of Siberian cities: Kemerovo (Shcheglovsk), Novokuznetsk (Stalinsk), Novonikolaevsk (the left bank of Novosibirsk).